Riding the glass escalator to the principal's office - Cognard-Black, Andrew J. (Teorija in praksa, 2012)
This study investigates the effect of workplace sex composition on men who do "women's work". Using data from 5,734 U.S. school teachers, I conduct multinomial logistic regression analyses to test hypotheses regarding men's and women's relative likelihood of moving out of teaching and advancing up into administrative positions. Results from these analyses provide no evidence that Kanter's tokenism proposition is generalizable to token men who teach in elementary schools; rather than suffering disadvantages, evidence supports Williams's "glass escalator" proposition that men enjoy privilege in predominantly female jobs and are more likely than women to be promoted into administrative positions.
Keywords: Delovno mesto; Workplace; Teachers; Učitelji; Spolna struktura (Demografija); Sex distribution (Demography); Job promotion; Napredovanje; United States; Združene države Amerike; delovna mesta; učiteljski poklici; spolna diskriminacija; United States of America; ZDA